An Analysis of the Bibliometrics of the Mexican Institute in Ophthalmology: A Case Study of an Emerging Research-Based Educational Health Institute - Lansingh, Van Charles; Lopez, Ellery; Gallo, Juan E.; Tuttle, Jared J.; Banuet-Martinez, Marina (Medical reference services quarterly, 2025)
The Instituto Mexicano de Oftalmología (IMO), a non-profit eye institute, has experienced significant growth. In this case study, we analyze IMO-affiliated publications (2012-2023) and introduce the Degree of Involvement in paper authorship index (DI-index). Journal metrics were extracted from InCites Journal Citation Reports and Scimago. IMO research output grew from one publication (2012) to 31 (2023), peaking at 45 (2018). The average impact factor rose from 0.2 (2012) to 5.2 (2022). The DI-index totaled 106.6 across 227 articles. Bibliometric analysis provides valuable insights for emerging institutions, and the DI-index provides a novel approach to evaluating authorship involvement.